Studi Material Isolator Panas Berbahan Dasar Serat Ijuk - Lukas Kano Mangalla; Budiman Sudia (Program Pendidikan Vokasi Teknik Mesin, 2021)
This research aims to investigate the value of thermal conductivity of a composite material made from Polyester Resin (R), Aren Fiber (I) and a some water and epoxy. Composite materials used in this work have been made based on the ASTM C177. Experimental apparatus used in this study consists of a source of heat (150 Watt), thermocouple, digital balance and stopwatch. The main materials on this study consist of the three variations of composition, 40%, 50% and 60% I/R (by volume) respectively. This work begins with preparation of the three specimen materials of each composition. All specimen have been made in 30cm x 30cm x 1 cm size of length, width and thickness, respectively, and investigated the properties of the composites at several spatial and time during applied some energy source. Investigation was conducted at ambient temperatures and pressure at each 1 minute for 120 minute of heating. Density of each composites composition was also measured for the same size of all specimen of 5cm x 5cm x 1cm with standard ASTM C 2005, respectively. The results of the study show that the properties of the composite material varies with material-based compositions. The higher the Resin the better the thermal conductivity of the composites. Volume fraction of 40% I/R has thermal conductivity (k) of 1.235 W / m ° C, volume fraction of 50% I/R has thermal conductivity of 1.129 W / m ° C and volume fraction of 60% I/R has Thermal conductivity of 1.077 W / m ° C. The density of the specimens of the volume fraction of 40%, 50% and 60%I/Ris 1177.962 kg / m³, 1155.386 kg/m³ and 1144.662 kg/m³ respectively. The result of analysis also shows that composition of 60% I/R seems to be the appropriate material isolator using in many engineering applications based on the lower thermal conductivity and lower density.